Agro-ecological bases for the adaptation of agriculture to climate change (UNED Research Journal, 2019)
Although many indigenous and peasant populations are particularly exposed to the impacts of climate change and are vulnerable, many communities are actively responding to the changing climate and have demonstrated innovation and resilience, using a variety of strategies to deal with droughts, floods, hurricanes, etc. In this article we argue that traditional agricultural systems offer a wide range of options and management designs that increase the functional biodiversity of crop fields, and therefore, reinforce the resilience of agroecosystems. Many of the traditional agroecological strategies that reduce vulnerability to climatic variability includes the diversification of crops, the maintenance of local genetic diversity, animal integration, the addition of organic matter to the soil, the harvesting of water, etc. Many agroecologists have deciphered the agroecological principles that underlie these strategies which can be adapted taking different technological forms (according to the size of the farms) to design modern agricultural systems so that they become increasingly resilient to the climatic extremes.
Keywords: Agroecology; traditional agriculture; adaptation; resilience; climate change